Flood-Irrigated Wheat Cost-Return Budget in Western Kansas - Dumler, Troy J.; Thompson, Curtis R. (My University, 2004)
This publication projects a budget that reflects expected income and costs based on flood-irrigated wheat production in western Kansas.
MF590_2004_10
Keywords: MF590; Economics; Crops; MF